Vision based context categorization for all-terrain robot - Chaínho, David Alexandre Calado Pereira (2011)
Dissertation presented at the Faculdade de Ciências e Tecnologia da Universidade Nova de Lisboa to obtain the Master degree in Electrical and Computer Engineering.